First evidence of SOX2 mutations in Peters' anomaly: Lessons from molecular screening of 95 patients. Issue 5 (27th February 2022) - Chesneau, Bertrand; Aubert‐Mucca, Marion; Fremont, Félix; Pechmeja, Jacmine; Soler, Vincent; Isidor, Bertrand; Nizon, Mathilde; Dollfus, Hélène; Kaplan, Josseline; Fares‐Taie, Lucas; Rozet, Jean‐Michel; Busa, Tiffany; et al.
Abstract: Peters' anomaly (PA) is a rare anterior segment dysgenesis characterized by central corneal opacity and irido‐lenticulo‐corneal adhesions. Several genes are involved in syndromic or isolated PA ( B3GLCT, PAX6, PITX3, FOXE3, CYP1B1 ). Some copy number variations (CNVs) have also been occasionally reported. Despite this genetic heterogeneity, most of patients remain without genetic diagnosis. We retrieved a cohort of 95 individuals with PA and performed genotyping using a combination of comparative genomic hybridization, whole genome, exome and targeted sequencing of 119 genes associated with ocular development anomalies. Causative genetic defects involving 12 genes and CNVs were identified for 1/3 of patients. Unsurprisingly, B3GLCT and PAX6 were the most frequently implicated genes, respectively in syndromic and isolated PA. Unexpectedly, the third gene involved in our cohort was SOX2, the major gene of micro‐anophthalmia. Four unrelated patients with PA (isolated or with microphthalmia) were carrying pathogenic variants in this gene that was never associated with PA before. Here we described the largest cohort of PA patients ever reported. The genetic bases of PA are still to be explored as genetic diagnosis was unavailable for 2/3 of patients. Nevertheless, we showed here for the first time the involvement of SOX2 in PA, offering new evidence for its role in corneal transparency and anterior segment development. Abstract :